Ritualization of Online Worship During COVID-19 Pandemic: A Case Study in GKMI ARK - Ayus Aditia Murwendayoko (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2023)
The COVID-19 outbreak that first happened in the city of Wuhan, China on January 2020 did not take long until it reached other parts of the world and then declared by World Health Organization as a pandemic within two month. In Indonesia, Mr. President Joko Widodo urged every citizen to do academic, economical, and religious activities at home in order to slow the spread of the virus. Christian congregations are among religious groups that had been affected by government’s measures to reduce the Coronavirus transmission. While online learning and remote working have been known and practiced by some, online worship was imaginable by none. Located within the “red area” where Coronavirus transmission is high, Gereja Kristen Muria Indonesia Anugerah Rayon Kembangan (GKMI ARK) was among the first churches in Indonesia to switch from on-site to fully online worship. The pastor and elders gave new set of rituals for online worship, to which the congregation must adapt, regardless of their preparedness. Ritual can be broadly defined as a set of meaningful sequence of actions produced by ritualization. This paper aims to explore the ritualization of online worship of GKMI ARK congregation during the COVID-19 pandemic.